FINANCIAL REGIMEN FROM THE CONSTITUTION OF 1993 - Rodríguez Cairo, Vladimir (2014)
This study addresses the constitutional provisions of the financial system in Peru and based on that, seeks to respond the question: Why should establish a financial regime in the Political Constitution?In that sense, it should be noted that the nature of the study is explanatory type. Similarly, research methods used are analytical and inductive. They also turned to secondary sources and the technique used was the document review.From this perspective, for a better understanding of the proposed theme, content is structured in three parts: the first comprises the foundation of financial regula-tion; in the second, the powers of the state organs in financial matters arise, and the third covers the finan-cial arrangements of the Constitution of 1993. Finally, conclusions are presented and disclosed the literature.